2020
DOI: 10.1111/rec.13292
|View full text |Cite
|
Sign up to set email alerts
|

A research agenda for the restoration of tropical and subtropical grasslands and savannas

Abstract: Despite growing recognition of the conservation value of grassy biomes, our understanding of how to restore biodiverse tropical and subtropical grassy biomes (grasslands and savannas; TGB) remains limited. Several tools have recently been identified for TGB restoration, including prescribed fires, appropriate management of livestock and wild herbivores, tree cutting and shrub removal, invasive species control, and the reintroduction of native grasses and forbs via seeding or transplants. However, additional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 103 publications
(138 reference statements)
1
58
0
2
Order By: Relevance
“…Wilsey (2021) identified several areas of need in grassland restoration research, several of which were also noted by Buisson et al (2021 a , 2021 b ). First, Wilsey (2021) pointed out that setting pre‐industrial vegetation as a restoration target of our actions is not feasible.…”
Section: Synthesis To Guide Grassland Restoration Across Scalesmentioning
confidence: 70%
See 3 more Smart Citations
“…Wilsey (2021) identified several areas of need in grassland restoration research, several of which were also noted by Buisson et al (2021 a , 2021 b ). First, Wilsey (2021) pointed out that setting pre‐industrial vegetation as a restoration target of our actions is not feasible.…”
Section: Synthesis To Guide Grassland Restoration Across Scalesmentioning
confidence: 70%
“…The papers of Buisson et al (2021 a , 2021 b ) and Wilsey (2021) identified several research gaps to be filled and challenges which grasslands face in the forthcoming decades. These include the (1) need for careful target vegetation selection and “climate‐adaptive” restoration; (2) lack of knowledge on the dynamics and restoration of several regions or grasslands types; (3) increased importance of the species arrival sequence and high likeliness of stochasticity of species establishment; and, finally, (4) issues of long‐term sustainability of restored sites/habitats in the form of post‐restoration management.…”
Section: Synthesis To Guide Grassland Restoration Across Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…The final chapter not only summarises the key threats to OEs in the context of global change, but particularly highlights important knowledge gaps and opens up new research questions and perspectives. This has already inspired a research agenda for the restoration of OEs (Buisson et al 2020).…”
Section: Content Of the Bookmentioning
confidence: 99%